PENGARUH MOTIVASI, KOMPETENSI DAN BUDAYA ORGANISASI PEGAWAI : (STUDI PADA DINAS PEKERJAAN UMUM KOTA CIMAHI) - Nursanty, Mia; Priadana, M. Sidik (Majalah Bisnis & IPTEK, 2013)
The company’s performace can be achieved if all exixting elements in the company well integrated and it focused on staffs at the Departement of Public Works where the roles, responsibilities and functions of the Public Works Departement is quite heavy because it deals directly with the public service. So that the employee’s performance will affect the public service. Thus, the human resources development is an essential part to improve the performance of the company.The main objective of the study was to determine how much influence the motivation, compentation and organization culture to the performance of employees. The study was conducted at Dinas Pekerjaan Umum Kota Cimahi, with all employees as the respondent, many as 114 people. The research method used is descriptive method of analysis to determine the level of motivation, competention, organizational culture and employee performance. To determine the Influence of motivation, compentation and organizational culture to the performance of employees, used verification method of analysis, which is processed by SPSS software. Based on the results of research proved that motivation give dominan influence to performance employee at 43,50%. Compentation influence to performance employee at 13,30%, and the organization culture influence on job satisfaction at 21,80%, while simultaneously motivation, compentation and organizational culture influence on the performance of employees at 78,6 %. To improve performance of employees, it is recommended to give more attention for performance of employees aspects such as reviewing work capacity to be more optimal, increased collaboration between the programs or programs related sectors to be sustainable, as well as complete the facilities of work. Keywords : motivation, competention, organization culture, employee performance.